The Impact of Timing and Mode of Delivery on the Outcome of Newborn with Gastroschisis - Hayder Neamah Hassan (Indian Journal of Forensic Medicine & Toxicology, 2021)
There are controversial data about of the most suitable method of delivery for the infants with pre- and ante-natal diagnosis of gastroschisis . The objective of the present study is to investigate the role of the gestational age and mode of delivery on the outcomes of infants with gastroschisis . Twenty seven infants diagnosed with gastroschisis were included in the current study . The study was conducted at Al-Zahra Teaching Hospital in Al-Najaf city, in Iraq , during the period between October 2017 to October 2020 . The results of the current study show that there is a significant relationship between each of mode of delivery and gestational age with type of surgery (p value = 0.04) . It also shows a high significant relationship between gestational age and age at presentation (p value = 0.01) . The study concluded that the outcome of newborn with gastroschisis might be slightly affected by timing and mode of delivery .